Politeness in the communication between humans and artificial intelligence - Alexander Ch. Piperski (Слово.ру: балтийский акцент)
The paper explores the evolution of communication etiquette between humans and artificial intelligence (AI), focusing particularly on the adaptation of traditional politeness strategies. While the politeness of AI can enhance the human level of trust, human politeness towards AI is equally important as it can impact the efficiency of communication. To demonstrate this, I conducted a pilot experiment with ChatGPT 4.0, using polite and non-polite prompts in Russian. The results suggest that politeness is likely to positively impact the accuracy of responses. Furthermore, the paper examines changes in speech etiquette, highlighting how interactions with AI often omit traditional greetings and farewells, reflecting a more functional approach to communication. Although the paper does not provide definitive answers on how politeness strategies between humans and AI should function, it underscores sociolinguistic points that are likely to become increasingly pressing over time. Overall, the paper illustrates a significant shift in communication practices, driven by the integration of AI into daily interactions, necessitating a reevaluation of the established social norms and speech etiquette.